Ultra Sound Evaluation of Asymptomatic Gall Bladder Perforation - Kumar P (Online Journal of Health & Allied Sciences, 2016)
Gall bladder perforation is a rare, fatal and life threatening complication of acute cholecystitis. A definitive diagnosis is uncommon before surgery due to which the morbidity and mortality associated with this condition is high. The delay in the diagnosis is attributed to the fact that most patients present with the same symptoms which can range from an acute generalized peritonitis to benign non-specific abdominal symptoms. We report a case of asymptomatic GB perforation which was confirmed on surgery.